Impact of TQM practices on innnovation performance among manufacturing companies in Malaysia - Choi Sang Long; Mohd Hamizan Abdul Aziz; Tan Owee Kowang; Wan Khairuzzaman Wan Ismail (South African Journal of Industrial Engineering, 2015)
This study examines the impact of total quality management (TQM) practices on an organisation’s innovation performance. Correlation coefficient and regression analysis is used to examine the relationship between TQM practices and innovation performance. This study’s sample is drawn from the manufacturing organisations located in the district of Rawang in the state of Selangor, Malaysia. The empirical results of this study confirm that TQM has a positive impact on innovation performance across five measured practices: customer focus, leadership, process management, strategic planning, and people management. Furthermore, the three most influential TQM practices are identfied as people management,process management, and customer focus. Managers in the manufacturing sector can find this study useful, especially if they are aiming to improve their organisation’s innovation performance with the help of quality management practices.